SYSTEMATIC LITERATURE REVIEW ON DIGITAL TRANSFORMATION IN THE ORGANIZATIONAL BUSINESS - Rian Bimo Ankhal; Muharman Lubis; Hanif Fakhurroja (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Digital transformation has become a crucial aspect of organizational strategies in various industries, including the business sector. This systematic literature review (SLR) focuses on understanding digital transformation within organizational business contexts. Through a systematic search of academic databases, The review explores key themes such as technological innovations, operational changes, customer-centric approaches, regulatory implications, and organizational adaptation. Technologies are driving significant changes, enabling organizations to streamline processes, enhance decision-making, and improve overall efficiency. Moreover, digital transformation is reshaping customer experiences, with personalized services and seamless interactions becoming essential for organizational success. Despite the benefits, organizations face challenges such as regulatory compliance, cybersecurity risks, and cultural resistance. By synthesizing existing research, this SLR aims to provide insights and guidance for organizations navigating the complexities of digital transformation in the organizational business landscape in the organizational business.